Fatigue while driving in a car simulator : effects on vigilance performance and autonomic skin conductance - Inkeri, Heidi (2010)
In this vigilance research the effect of fatigue on driver’s voluntary reaction times (RT) and autonomic skin conductance (SC) was studied. Participants (n=17) drove approximately 3 hours in a simulator responding simultaneously on a peripheral visual vigilance task (PVVT). RTs were classified into 5 quintiles according to their latency. Also misses and misclassifications were explored. Results indicated that RTs increased linearly over time. SC amplitudes differed significantly between RT quintiles. Vigilance performance was the best when arousals were frequent but their magnitude remained relatively low. Frequent and high amplitude arousals in turn were associated with the worst performance. Results suggest that autonomic SC and voluntary RT could be combined to reveal driver’s fatigue and vigilance performance more consistently than either measure alone.